1973
DOI: 10.1021/ma60032a011
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Isotactic Poly(tert-butylethylene oxide)

Abstract: bands. The ratios of the 367-to the 412-nm band also agrees reasonably well with the calculated sequence ratios. However, since the bands become closer together as we go to higher wavelengths, overlapping becomes more severe and the intensity measurements, particularly of the 412-nm band, are less precise.The agreement of the observed ratios with the calculated ratios supports the original assignments of the sets to Isotactic Poly(£ert-butylethylene oxide) Studies 205 diads, triads, tetrads, and pentads derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…1 Tadokoro showed that poly(tertbutylene oxide) and poly(tert-butylene sulfide) form racemic lattices, in which R-and S-chains are arranged side by side in 1/1 proportion. 2,3 Firstly, it was reported in 1987 that PLLA and poly(D-lactide) (PDLA) crystallize into a 1/1 stereocomplex which exhibits a 50°C higher melting point than the enantiomeric components. 4 In the last years many investigations were carried out concerning the physical properties of the stereocomplex.…”
Section: Introductionmentioning
confidence: 99%
“…1 Tadokoro showed that poly(tertbutylene oxide) and poly(tert-butylene sulfide) form racemic lattices, in which R-and S-chains are arranged side by side in 1/1 proportion. 2,3 Firstly, it was reported in 1987 that PLLA and poly(D-lactide) (PDLA) crystallize into a 1/1 stereocomplex which exhibits a 50°C higher melting point than the enantiomeric components. 4 In the last years many investigations were carried out concerning the physical properties of the stereocomplex.…”
Section: Introductionmentioning
confidence: 99%
“…However, by comparison, stereocomlexation is still a rare yet interesting phenomenon in polymers. Several cases have been found by blending tactic polymers of opposite configurations, for examples, isotactic and syndiotactic poly(methyl methacylate)s, 2,3 polythiiranes, 4 polyoxiranes, 5 polylactones. 6,7 The common features of all these systems are that crystallization of enantiomeric polymer chains leads to packing of two different molecular chains into a common crystal lattice, in which the two chains are more densely packed than those of the parent homopolymer crystal lattices.…”
mentioning
confidence: 99%
“…This was demonstrated by Ikada et al (1987) in a study using X-ray diffraction, which showed the differences of crystalline structure in the formation of a stereocomplex of PDLA and PLLA blending. Tsuji et al (1991) quoted the findings of Sakakihara et al (1973) that when an equimolar ratio of optically active polymers are blended together, the optical compensation of the stereopolymer occurs, leading to inactive materials in the crystalline region or unit cell. The side-by-side packing of stereo complexes can be expected to form a compact, ordered structure with a high melting temperature.…”
Section: Thermal Transition and Crystallization Of Plamentioning
confidence: 98%